Akurasi dan Efektivitas Block Adjustment Menggunakan Titik Kontrol Peta Foto untuk Peningkatan Kualitas Data Bidang Tanah Studi Kasus di Kabupaten Sleman - Perkasa, Desga; Nugroho, Tanjung; Widiyantoro, Susilo (Kadaster: Journal of Land Information Technology, 2025)
This study analyzes the accuracy and effectiveness of block adjustment in improving cadastral data quality by comparing two sources of control points: field measurements using GNSS Real Time Kinematic (RTK) and the interpretation of high-resolution aerial photomaps. The main issue addressed is the inconsistency of parcel coordinates in the PTSL program, particularly in areas that are difficult to access. This research fills the gap by evaluating the use of photomap control points as a practical alternative. The study was conducted in Banyuraden Village, Sleman Regency, involving 72 land parcels across three blocks. Data were quantitatively processed using the PEREKAT plugin in QGIS. Photomap control points had a resolution of GSD ≤ 0.12 m and positional accuracy of CE90 ≤ 0.4 m. Distance and area accuracy tests referred to PMNA/KBPN No. 3/1997 and ATR/BPN Regulation No. 21/2019, while effectiveness was assessed using a tolerance of 5% of the survey plan area. The results indicate that validation effectiveness using photomap control points reached 86.57%, compared to 88.06% with field-based control points. Both values fall within the “highly effective” category (ratio ≥ 80%). The small difference in effectiveness highlights that photomap control points can serve as an efficient alternative for cadastral mapping in hard-to-reach areas and support the acceleration of digital land administration services. Keywords: Block Adjustment, Photomap Accuracy, GNSS RTK, PTSL, Digital Land Administration INTISARI Penelitian ini menganalisis akurasi dan efektivitas block adjustment untuk meningkatkan kualitas data pertanahan dengan membandingkan dua sumber titik control, yaitu pengukuran lapangan berbasis GNSS Real Time Kinematic dan interpretasi peta foto udara resolusi tinggi. Permasalahan yang diangkat adalah ketidaksesuaian koordinat bidang tanah dalam program PTSL, khususnya pada wilayah yang sulit dijangkau. Penelitian ini mengisi gap dengan mengevaluasi penggunaan titik kontrol peta foto sebagai alternatif. Studi dilakukan di Kalurahan Banyuraden, Kabupaten Sleman, melibatkan 72 bidang tanah pada tiga blok. Data dianalisis secara kuantitatif menggunakan plugin PEREKAT pada QGIS. Titik kontrol peta foto memiliki resolusi GSD ≤ 0,12 m dan ketelitian CE90 ≤ 0,4 m. Uji akurasi jarak dan luas mengikuti ketentuan PMNA/KBPN No. 3/1997 dan Permen ATR/BPN No. 21/2019, sedangkan uji efektivitas menggunakan toleransi 5 % luas surat ukur. Hasil menunjukkan bahwa efektivitas validasi dengan titik kontrol peta foto mencapai 86,57%, sedangkan dengan kontrol lapangan 88,06%. Keduanya masuk kategori “sangat efektif” (rasio ≥ 80%). Selisih efektivitas yang kecil menegaskan bahwa titik kontrol peta foto dapat menjadi alternatif efisien dalam pemetaan bidang tanah di wilayah sulit diakses serta mendukung percepatan digitalisasi layanan pertanahan. Kata Kunci: Block Adjustment, Akurasi Peta Foto, GNSS RTK, PTSL, Digitalisasi Layanan Pertanahan